Compare the Effectiveness of Carbimazole Single Dose and Divided Dose Regimens for Euthyroid Induction in Hyperthyroid Patients - Aamir Khan, Muhammad Shoaib Khan, Atif Iqbal, Muhammad Hamza Tahir, Mohammad Basil Rizvi, Muhammad Amir Murtaza (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of the current study was to examine the effectiveness of carbimazole administered as a single dose with a divided dose regimen for inducing euthyroidism in hyperthyroid patients. Study Design: Prospective/Randomized study Place and Duration: This Prospective/Randomized study was conducted at Khyber Teaching Hospital Peshawar in the duration from June, 2022 to November, 2022. Methods: There were 92 patients of hyperthyroidism were presented in this study. Age, sex, BMI, and residency details for each enrolled case were recorded after receiving informed written consent. Patients were divided into two groups equally. Carbimazole (OD-CMZ) was administered as a single dosage to 46 patients in group I, and as two separate doses to 46 patients in group II (DD-CMZ). For six months, the effectiveness of the treatment was monitored on a regular basis (every four weeks). SPSS 22.0 was used to analyze all data. Results: There were 54 (58.7%) females and 38 (41.3%) males in this study. In group I mean age was 35.13±6.60 years and in group II mean age was 40.10±8.86 years. Mean duration of disease was 3.6±10.57 months in group I and in group II mean duration was 4.3 ±8.35 months. There was no discernible difference between the two groups in terms of baseline TSH and T4 concentrations or their cumulative rates of reduction (p-value, 0.014). Frequency of euthyroidism in group I after final follow up was 46 (100%) and in group II found in 45 (97.8%) cases but difference is insignificance. Conclusion: In this study, we came to the conclusion that a single dosage regimen is a more effective way to treat hyperthyroidism since there is no discernible difference in efficacy and a greater risk of developing hypothyroidism with a split dose strategy. Keywords: Hyperthyroidism, Drug therapy, Single dose, Carbimazole, Multidose